The relationship between organisational characteristics and disclosures in non-profit organisations / Nurfarahin Roslan - Roslan, Nurfarahin (2014)
Provision of a comprehensive annual reports fromnon-profit organizations (NPOs) is crucial in order to enhance credibility, build community trust and demonstrate their responsiveness towards stakeholders.Existed for the benefit of public as the principal objective, NPOs highly depend on the external environment to ensure sustainability of operations.However, since NPOs are subjected to minimum regulatory requirement, this situation triggers some major problems which reduce NPOs value and reputation. Hence, the objective of this study is to examine the relationship between social enterprise initiative, management commitment and financial vulnerability with the level of information disclosed in the annual report of NPOs in Malaysia. Content analysis was employed as a method to assess the annual reports of 205 NPOs registered with Registrar of Societies (ROS) in Malaysia for the financial year 2011. Findings of this study revealed that the total disclosures among sample NPOs was weak especially the disclosures in Balance Sheet (BS) and Statement of Financial Activities (SOFA). Within the three major component of total disclosures, NPOs disclosed a relatively high nonfinancial information as compared to the financial information. With regards to the independent variables tested, the study found that social enterprise initiatives and management commitment are significantly associated with the level of information disclosed in annual report. In adverse, financial vulnerability was found insignificant to the overall disclosures. Of relevance, statistical analysis also revealed that most of the NPOs in Malaysia were in financially vulnerable condition. In addition, commitment anticipated from the non-profitmanagers are quite low among the sample NPOs. Overall, the findings provide a useful information to regulators to continuously improve the nonprofit sector through developing more comprehensive framework and practices in assisting preparation and presentation of NPOs annual reports.